Pengaruh Bahan Kimia Tawas terhadap Nilai CBR Serta Penurunan Tanah Berdasarkan Pengujian Konsolidasi pada Tanah Lempung - Dendi Yogaswara; Dini Destiani Siti Fatimah; Ayu Sri Rahayu (Institut Teknologi Garut, 2025)
This study was conducted precisely in Lebakjaya Village, Karangpawitan District, an area that will be traversed by the construction of the Gedebage-Tasikmalaya-Cilacap (Getaci) toll road. The soil in this location exhibits clay characteristics with a Plasticity Index (PI) value of 21.13%. The research aims to determine significant changes in CBR and consolidation values obtained from various mixture compositions.The methodology employed in this study was experimental, involving a series of laboratory tests for observation. These tests included physical soil property testing, CBR testing, and consolidation testing, all conducted to evaluate changes in soil bearing capacity and settlement behavior.The results showed that, according to the AASHTO classification system, the soil falls under group A6, indicating a clayey soil type with a high plasticity index. The CBR test demonstrated an optimum improvement at a 5% mixture variation, yielding a CBR value of 10.37%. Meanwhile, consolidation testing revealed that mixture variations of 5%, 10%, and 15% reduced the consolidation settlement (Sc), while the coefficient of consolidation (Cv) increased at 5% and 10% variations.These findings suggest that the use of aluminum sulfate (alum) as an additive is feasible. However, the selected mixture percentage must carefully consider the moisture content, as this significantly influences the chemical reaction between water and aluminum sulfate.